Pengaruh Diabetes Self Management Education and Support (DSME/S) terhadap Diabetes Distress pada Pasien Diabetes Melitus Tipe 2 di RSD dr. Soebandi Jember (The Effect of Diabetes Self Management Education and Support [DSME/S] on Diabetes Distress in Patie - Novita Nurkamilah; Rondhianto Rondhianto; Nur Widayati (UPT Percetakan dan Penerbitan Universitas Jember, 2018)
Diabetes Mellitus (DM) is a chronic disease that requires a continous self-care. A low level ofknowledge about self-care can worsen health condition and cause diabetes distress. The continuingstress can cause hyperglycemia that lead to complications of DM. DSME/S is a structured healtheducation that facilitates DM patients in implementing and maintaining their behavior for sustainableself-care. This research aimed to analyze the effect of DSME/S on diabetes distress in patients withtype 2 DM. This research was quasi experimental with non randomized control group pretestposttest design. Thirty respondents in this study were divided into 15 respondents as theintervention group and 15 respondents as the control group by consequtive sampling technique.DSME/S was conducted in 6 sessions: 4 sessions in the hospital and 2 sessions at respondent'shouse. The data were analyzed by using dependent t test and independent t test with significancelevel of 0.05. The result of dependent t test revealed a significant difference of diabetes distressbetween pretest and posttest both in the intervention group (p=0.001) and in the control group(p=0.046). Furthermore, independent t test showed a significant difference between interventiongroup and control group (p=0.001). The decrease of diabetes distress was higher in the interventiongroup than control group. This result indicates that there was a significant effect of DSME/S ondiabetes distress in patients with type 2 DM. Nurses are expected to apply DSME/S as a dischargeplanning to reduce diabetes distress in patients with type 2 DM.Keywords: diabetes distress, DSME/S, Diabetes Mellitus